Pengaruh Motivasi Dan Tunjangan Kinerja Terhadap Kinerja Pegawai Dengan Produktivitas Sebagai Variabel Intervening Pada Dinas Pendidikan Kabupaten Jember - Ni Nyoman Putu Martini; Eko Budi Satoto; Maret Wijayati (Institut Teknologi dan Sains Mandala, 2025)
Performance is the implementation of a job and the improvement of that work in accordance with one's responsibilities so that the results can be achieved as expected. Motivation, performance allowances, productivity are some of the factors that support performance. The aim of this research is to determine directly or indirectly the influence of motivation and performance allowances on employee performance with productivity as a mediating variable at the Jember district education office. The number of samples in this study was 221 respondents, namely employees with ASN status. The analysis technique used is Structural Equation Model (SEM) using the WarpPLS 7.0 application. The results of data analysis show (1) motivation variables do not directly have a significant effect on employee productivity and performance (2) performance allowances directly have a significant effect on employee productivity and performance. (3) the productivity variable directly has a significant effect on performance (4) motivation has no significant positive effect on employee performance through productivity (5) performance allowances have a significant positive effect on employee performance through productivity.